Rhinitis in elite and non-elite field hockey players - Walker, A.; Surda, P.; Rossiter, M.; Little, S. (International Journal of Sports Medicine, 2017)
Rhinitis has been demonstrated to impose a significant disease burden upon the general population. We sought to determine the prevalence of rhinitis in athletes; to investigate its relationship with co-existing allergic symptoms; and to quantify the impact of rhinitis on quality of life in the athlete.3 subgroups were studied: elite field hockey players (FHP); non-elite FHP; and a sedentary control group.Participants were asked to complete a rhinitis self-report questionnaire; the "Allergic Questionnaire for Athletes" (AQUA), and quality of life Sinonasal Outcome Test - 22 (SNOT-22).142 participants completed the study (52 elite FHP; 40 non-elite FHP; 50 controls). There was a significantly higher prevalence of rhinitis in the elite and non-elite FHP groups than the sedentary control group (52% and 43% vs. 22%, p<0.05). Mean AQUA score was significantly higher in athletes with rhinitis. Quality of life scores were significantly worse in athletes with rhinitis than those without rhinitis (p<0.05).This study suggests regular exercise is associated with a significant increase in the prevalence of rhinitis. Elite FHP were most likely to report rhinitis, but the least likely to be using regular treatment. Quality of life was negatively affected, confirming the importance of nasal health to athlete welfare.